Retinal changes in febrile seizures in children: a retrospective analysis in Tuzla Canton, Bosnia and Herzegovina - Meliha Halilbašić; Amra Nadarević Vodenčarević; Anis Međedović; Amir Halilbašić; Almira Ćosićkić; Ajla Pidro (Medicinski Glasnik, 2021)
Aim To evaluate the possibility of retinal haemorrhages or any other retinal pathology caused by febrile seizures alone in children aged between 2 months and 15 years. Methods Children aged between 2 months and 15 years admitted to the hospital following seizures were examined within 48 hours of admission. The seizures were classified by a paediatric neurologist and a detailed ocular examination, including indirect ophthalmoscopy, was performed by an ophthalmologist. Results In the period between May 2019 and May 2020 a total number of 106 children were examined. There were 66 (62.3%) male and 40 (37.7%) female children. The youngest patient was 2 months old and the oldest patient was 15 years old. None of the children was found to have retinal haemorrhages or any other retinal pathology. Conclusion Retinal haemorrhages or any other acute retinal findings in children with febrile seizures are very rare, but we cannot rule out its occurrence. The finding of retinal haemorrhages in a child admitted with a history of seizure should trigger a detailed search for other causes of those haemorrhages, especially shaken baby syndrome. Due to the lack of any manifestations on the retina after febrile seizure, maybe it is time that the current protocol and guidelines, considering obligatory fundus examination, should be re-examined.